Electrochemical behavior of stainless - steel versus nickel - titanium endodontic files in different irrigating solutions - Nevine Abdallah Mohamed Moussa; Lubna Abbas Shafie; Nadia Amin Badr (Cairo : Nevine Abdallah Mohamed Moussa, 2008)
The present study was performed to study the electrochemical behavior of stainless steel and nickel titanium hand files in different irrigating solutions . A total of eighty K - type hand files # 45 were used : 40 SS K - type and 40 NiTi Flex K - type files . The files of each type were equally divided into two categories ; twenty files each
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Endodontics
Issued also as CD
Keywords: Endodontic irrigants; Nickel titanium files; Stainless steel files